Anti–Interferon‐Inducible Protein 16 Antibodies Associate With Digital Gangrene in Patients With Scleroderma. Issue 5 (May 2016) - McMahan, Zsuzsanna H.; Shah, Ami A.; Vaidya, Dhananjay; Wigley, Fredrick M.; Rosen, Antony; Casciola‐Rosen, Livia
Abstract : Objective: To examine the association between anti–interferon‐inducible protein 16 (anti–IFI‐16) antibodies and clinical features of scleroderma. Methods: Sera from a discovery sample of 94 patients with scleroderma and 47 healthy controls were assayed for anti–IFI‐16 antibodies by enzyme‐linked immunosorbent assay, and associations were examined using regression analyses. Since anti–IFI‐16 autoantibodies were found to be strongly associated with digital gangrene in the discovery sample, a subsequent case–control study (with subjects matched 1:1 on disease duration) was designed for further exploration. Cases were patients with scleroderma and digital gangrene, while controls were patients with scleroderma and Raynaud's phenomenon alone (n = 39 matched pairs). Nonparametric, unadjusted matched pairs analysis as well as univariate and multivariable conditional logistic regression analyses were performed. Results: In the discovery sample, anti–IFI‐16 antibodies were more prevalent in patients with scleroderma than in healthy controls (18% versus 2%; P = 0.01). Patients with anti–IFI‐16 antibodies, compared to anti–IFI‐16 antibody–negative patients, were more likely to have limited scleroderma (77% versus 46%; P = 0.03), a longer disease duration (median 15.2 years [interquartile range 10.6–18.3] versus 6.0 years [interquartile range 3.4–13.8]; P < 0.01), digital gangrene (24% versus 4%; P = 0.02), and a low diffusing capacity for carbon monoxide (DLco ) ( P < 0.01). In the case–control study, 35 (45%) of 78 patients were anti–IFI‐16 antibody positive. Anti–IFI‐16 antibody levels were significantly higher in cases with digital gangrene than in matched controls ( P = 0.02). In analyses adjusted for age, cutaneous scleroderma subtype, smoking, and DLco, high anti–IFI‐16 antibody levels were associated with the presence of digital gangrene (adjusted odds ratio 2.3, 95% confidence interval 1.0–5.6, P = 0.05). The odds of having digital gangrene increased with higher anti–IFI‐16 antibody titers, in a dose‐dependent manner. Conclusion: Anti–IFI‐16 antibodies are associated with digital gangrene in patients with scleroderma. Longitudinal prospective studies exploring anti–IFI‐16 antibodies as a disease biomarker, and biologic studies investigating the pathogenicity of these antibodies, are warranted.